Malaysian green building index (GBI) and its application for green mosques : the literature review / Muhammad Akram Ismail, Nur Azfahani Ahmad and Nadiyanti Mat Nayan - Ismail, Muhammad Akram; Ahmad, Nur Azfahani; Mat Nayan, Nadiyanti (2019)
Malaysia has undergone over 50 years of rapid industrialisation, recording 5% to 9% of Growth Domestic Product (GDP) growth annually. The industrialisation has sprawled from urban areas to rural areas, giving more prosperous economic development. Unfortunately, most of the development has been unsustainable and there is a need for a holistic move towards sustainable approaches for the development, especially for the public building, like mosque. Simultaneously, Malaysian Green Building Index (GBI) is created to support these sustainable approaches for mosque. However, there are limitations on the green element’s application especially for existing mosques, since there is typical mindset from the building owners that the GBI application procedures is hinder with complicated procedures. This paper will explore the literature review of the relationship between Malaysian Green Building Index (GBI) and its Application for Green Mosques in Malaysia.